The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.18632/oncotarget.4358
|View full text |Cite
|
Sign up to set email alerts
|

Radio-resistant mesenchymal stem cells: mechanisms of resistance and potential implications for the clinic

Abstract: Mesenchymal stem cells (MSCs) comprise a heterogeneous population of multipotent stromal cells and can be isolated from various tissues and organs. Due to their regenerative potential, they have been subject to intense research efforts, and they may provide an efficient means for treating radiation-induced tissue damage. MSCs are relatively resistant to ionizing radiation and retain their stem cell characteristics even after high radiation doses. The underlying mechanisms for the observed MSC radioresistance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 141 publications
(161 reference statements)
3
73
1
Order By: Relevance
“…Chk1 and Chk2 are main inhibitors of Cdc25A and Cdc25C resulting in Cdk/cyclin-mediated cell cycle arrest [71]. It has been suggested that DSB in MSCs are repaired by activation of both the homologous recombination (HR, during S and G2 phases) and the non-homologous end-joining (NHEJ, during all cell cycle phases) DNA repair pathways [95,104,106]. Our recent study showed the activation of HR and NHEJ repair pathways in irradiated aMSCs [159].…”
Section: Mesenchymal Stromal Cells (Mscs) Radio-biological Responsementioning
confidence: 97%
See 4 more Smart Citations
“…Chk1 and Chk2 are main inhibitors of Cdc25A and Cdc25C resulting in Cdk/cyclin-mediated cell cycle arrest [71]. It has been suggested that DSB in MSCs are repaired by activation of both the homologous recombination (HR, during S and G2 phases) and the non-homologous end-joining (NHEJ, during all cell cycle phases) DNA repair pathways [95,104,106]. Our recent study showed the activation of HR and NHEJ repair pathways in irradiated aMSCs [159].…”
Section: Mesenchymal Stromal Cells (Mscs) Radio-biological Responsementioning
confidence: 97%
“…These mechanisms were also shown to be responsible for the IR resistance of cancer stem cells (CSC), also known as cancer initiating cells, which have been linked to cancer disease recurrence and aggression [100][101][102][103]. These mechanisms were tested in bmMSCs in earlier studies showing that these bmMSCs are relatively radio-resistant [95,96,[104][105][106]. Do MSCs from different tissue origins behave similarly?…”
Section: Mesenchymal Stromal/stem Cells Therapymentioning
confidence: 99%
See 3 more Smart Citations